Statistical arbitrage in cryptocurrency market - Rozbeiko, Ruslan (2019)
The main purpose of the bachelor thesis is focused on applying statistical arbitrage strategy – pairs trading on cryptocurrency market. This work introduces theory behind statistical arbitrage and pairs trading. History and current state of cryptocurrency market is analysed with future description of selected cryptocurrencies, their history and underlying technology. For pairs trading 3 methods are analysed: Engle-Granger 2 step method, Johansen test and bivariate copulas. Analysis showed that bivariate copulas approach has the best performance on backtest. Bivariate copulas approach is also the only profitable approach out of those 3 after considering slippage and commission in backtest model.